Research and application of locomotive wheel reprofiling model targeting flange thickening - LIU Tong; WEN Shihu; XU Huawei; CHENG Yaping (机车电传动)
Flange thickness is an important parameter measuring wheel size of locomotives. In recent years, the problem of flange thickening over the specified limit has become particularly prominent, which not only increases the maintenance cost, but also reduces the locomotive turnover rate. Moreover, excessive losses due to reprofiling bring an adverse effect to the service life of wheels. In this paper, the principle of flange thickening was firstly analyzed, and it was found that the change in measurement standard and the improvement of locomotive operating track conditions are the main influencing factors. A flange thinning model was built based on the wheel tread contours with thin flanges specified in the Chinese railway standard, and analysis was performed in consideration of the actual flange change of each wheel, to generate the reprofiling plans to maintain their wheel tread contours with the optimum flanges. In addition, the flange thinning model was added to the economical reprofiling model, and the technical indicators such as flange thickness, reprofiling amount, reprofiling order, and reprofiling craft requirements were determined, integrating the factors such as the initial reprofiling amount and the requirements of wheel diameter difference into account, such achieving customization for wheel reprofiling plans, and expanding the application scope of economical reprofiling model. An application system was built based on the improved wheel reprofiling model, which was applied in trial to the locomotive wheels at the depot, and the improved model was verified in actual conditions. In the two-month trial application, flange thinning reached a proportion of 78%, with an average thinning of 0.83 cm and the average reprofiling amount per wheel down by 7.94%. It can be seen from the verification results that the model can not only reduce the reprofiling proportion of locomotives with thickened flanges, thus improving the turnover rate of locomotives, but also effectively reduce the average reprofiling amount of wheels, to prolong their service life, demonstrating the value of promotion and application.